Omahe Rak Usah Apik-Apik: Adequate Housing Problems of the Urban Poor along Railway Tracks - -, Syahwal (UI Scholars Hub, 2025)
As urban development accelerates, urbanization has simultaneously grown as an inseparable phenomenon. However, beneath this transformation lies a crisis within the capitalist system known as overaccumulation, which has led to the marginalization of urban poor groups. This phenomenon results in the creation of slums, one of which is found in the periphery of railway tracks, where the urban poor reside. Semarang the capital of Central Java Province, Indonesia, is an apt example of such developments,. This study takes as starting point that the right to adequate housing is an integral part of human rights and addresses the issue of why the right to adequate housing is not realized for those living on the outskirts of railway tracks. Using a socio-legal approach and drawing on a critical geography conceptual framework, this research reveals that the realization of the right to adequate housing in these areas is hindered by vulnerability to eviction, a consequence of the capitalist-driven urban development paradigm. Moreover, human rights approaches tend to be liberal, based on the assumption that all individuals are equal before the law, without considering the spatial context that influences how these rights are constrained and, therefore, difficult to realize.